PENGARUH RASIO LIKUIDITAS, PROFITABILITAS, STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR BATUBARA DI BEI TAHUN 2017-2021 - Muhamad Fadilla Putra Soelaksana (2022)
The purpose of this study was to determine the effect of company performance as proxied by Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) in determining company value also proxied by price book value (PBV) in the coal sub-sector. listed on the Indonesia Stock Exchange in 2017-2021. This research is a quantitative research. The population used in this study is the coal sub-sector companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used purposive sampling which obtained 24 companies as research samples for three years and obtained as many as 120 research sample units. Data analysis using EViews 12 and Microsoft Excel 2020 5% significance level. The research results obtained from data processing are that profitability (ROA) has no effect on firm value (PBV), capital structure (DER) has a significant positive effect on firm value (PBV). Liquidity (CR) has no effect on firm value.